Inhibition of SOS Response by Nitric Oxide Donors in Escherichia coli Blocks Toxin Production and Hypermutation - Crane, John K.; Burke, Sarah R.; Alvarado, Cassandra L. (Frontiers in Cellular and Infection Microbiology, 2021)
Background Previous reports have differed as to whether nitric oxide inhibits or stimulates the SOS response, a bacterial stress response that is often triggered by DNA damage. The SOS response is an important regulator of production of Shiga toxins (Stx) in Shiga-toxigenic E. coli (STEC). In addition, the SOS response is accompanied by hypermutation, which can lead to de novo emergence of antibiotic resistance. We studied these effects in vitro as well as in vivo. Results Nitric oxide donors inhibited induction of the SOS response by classical inducers such as mitomycin C, ciprofloxacin, and zidovudine, as measured by assays for E. coli RecA. Nitric oxide donors also inhibited Stx toxin protein production as well as stx2 RNA in vitro and in vivo. In vivo experiments were performed with ligated ileal segments in the rabbit using a 20 h infection. The NO donor S-nitroso-acetylpenicillamine (SNAP) reduced hypermutation in vitro and in vivo, as measured by emergence of rifampin resistance. SNAP blocked the ability of the RecA protein to bind to single-stranded DNA in an electrophoretic mobility shift assay (EMSA) in vitro, an early event in the SOS response. The inhibitory effects of SNAP were additive with those of zinc acetate. Conclusions Nitric oxide donors blocked the initiation step of the SOS response. Downstream effects of this blockade included inhibition of Stx production and of hypermutation. Infection of rabbit loops with STEC resulted in a downregulation, rather than stimulation, of nitric oxide host defenses at 20 h of infection.